THE STATE OF SOIL POLLUTION IN THE AKMOLA REGION AND WESTERN KAZAKHSTAN WITH HEAVY METALS - Yertas Bitmanov; Akhan Abzhalelov; Laura Boluspayeva (Reviews of Modern Science, 2026)
A survey was conducted in seven cities of Central and Western Kazakhstan, with soil samples collected from industrial, residential, transport, and background zones. Laboratory analyses were carried out to determine the concentrations of heavy metals and to assess the level of environmental pressure. The study focused on soils in areas affected by industrial and energy enterprises, which serve as indicators of the ecological state of the regions. The results allow for the identification of zones of technogenic contamination and the determination of spatial patterns in heavy metal distribution, which is essential for ongoing monitoring and for developing measures to reduce environmental pressure in the studied areas